A Mixed-Method Analysis of Fatal Attacks on Police by Far-Right Extremists. (June 2016) - Gruenewald, Jeff; Dooley, Kiefer Michael G.; Suttmoeller, Michael J.; Chermak, Steven M.; Freilich, Joshua D.
Several recent high-profile homicides of police officers have brought increased attention to issues of far-right extremist violence in the United States. We still, however, know very little about why (and how) certain encounters between far-right extremists and police result in violence. To fill this research gap, we conduct a mixed-method analysis of far-right antipolice homicides based on quantitative and qualitative data from the U.S. Extremist Crime Database. We begin by categorizing cases based on key aspects of homicide storylines. We then comparatively analyze attributes of event precursor, transaction, and aftermath stages across four storyline categories. Finally, a case study is purposively selected to follow-up on each storyline category to better capture the nuances of fluid homicide processes. Our findings have important implications for identifying triggering events, escalation factors, and other situated sets of conditions and circumstances that contribute to deadly outcomes for police officers.